John W. Leonard correspondence - Leonard, John W.
ALS (1856 July 4; Japan Sea) written by Leonard, probably as master of the ship Lydia of Fairhaven, Mass., on a voyage to the North Pacific, to his wife Sylvia in New Bedford, Mass. Notes that one whale has been taken with hopes for more success in the Okhotsk Sea. Also mentions the catch of the ship Fabius out of New Bedford. Includes ALS (1857 December 22; Honolulu, Hawaii) in which Leonard expects to be home in May.
Master of whaling ship.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Leonard, Sylvia -- Correspondence; Fabius (Ship); Lydia (Ship : 1840-1864); Whaling -- Japan, Sea of; Whaling -- Okhotsk, Sea of; Honolulu (Hawaii) -- Description and travel; Whalers (Persons)